2017
DOI: 10.20959/wjpps20175-9135
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus: Role of Free Radicals and Oxidative Stress

Abstract: ABTRACTFree radical defined as an atom or molecule containing one or more unpaired electrons in valence shell or outer orbit and is capable of independent existence. Because of non-bonding electrons, free radicals have affinity to react with other compounds and act as electron acceptors or oxidizing agents. Main oxidants include reactive oxygen species (ROS), nitrogen (RNS), chloride (RCS) and sulfur. The most main antioxidant and major cause of oxidative damage to the body"s biomolecules is ROS. ROS are well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 76 publications
0
8
0
3
Order By: Relevance
“…Such changes in the masticatory muscle of MF are caused by several factors. First, hyperglycemia promotes glycosylation of proteins (actin and myosin), which in turn are chemically modified [8] and lead to other complications associated with type 1 diabetes [9]. Some researchers found an increased content of glycosylation end products in proteins of skeletal muscle which led to a decrease in the mobility of actin and myosin, causing a glucose-dependent decrease in myofibril function [10].…”
Section: експериментальні дослідженняmentioning
confidence: 99%
“…Such changes in the masticatory muscle of MF are caused by several factors. First, hyperglycemia promotes glycosylation of proteins (actin and myosin), which in turn are chemically modified [8] and lead to other complications associated with type 1 diabetes [9]. Some researchers found an increased content of glycosylation end products in proteins of skeletal muscle which led to a decrease in the mobility of actin and myosin, causing a glucose-dependent decrease in myofibril function [10].…”
Section: експериментальні дослідженняmentioning
confidence: 99%
“…Не менш важливою проблемою хворих на ЦД є ураження центральної нервової системи (ЦНС), у тому числі внаслідок підвищеної продукції вільних радикалів, виснаження антиоксидантних механізмів і розвитку окисного стресу [1]. До факторів, що підвищують чутливість нейронів до прооксидантно-антиоксидантного дисбалансу, відносять розлади аксоплазматичного транспорту, порушення продукції енергії в клітинах головного мозку (ГМ), що спричиняє вторинне пошкодження трансмембранного іонного транспорту [2]. Також патогенетичною складовою діабетичних ускладнень з боку ЦНС є порушення кровообігу, оскільки ендотелій кровоносних судин, як і нейрони, належить до тканин, що поглинають глюкозу незалежно від вмісту інсуліну.…”
Section: вступunclassified
“…Отримані нами результати узгоджуються з літературними даними про те, що досліджуваний показник зростає внаслідок розкладу поліненасиче-них жирів формами кисню з високою реакційною здатністю та є маркером пошкодження клітинних мембран [2,3,8]. У групі щурів з ЦД 2-го типу після введення карбацетаму вміст ТБКАП знижувався як у корі головного мозку (на 11,9 %), так і в гіпокампі (на 28,1 %) порівняно з нелікованими тваринами.…”
Section: обговоренняunclassified
See 1 more Smart Citation
“…It has been reported that the free radical scavengers are effective in avoiding diabetes in animal models. 3336 However, recent shreds of evidence have revealed that first-line therapy for cardiovascular disease prevention and the most important lipid-lowering drugs such as statins can increase the risk of new-onset diabetes. 37,38 It is assumed to have a direct correlation between antidiabetic and antioxidant potentials of compounds.…”
Section: Introductionmentioning
confidence: 99%